Ultrasound Monitoring of Umbilical Catheters in the Neonatal Intensive Care Unit—A Prospective Observational Study - Sobczak, Alina; Dudzik, Aleksandra; Kruczek, Piotr; Kwinta, Przemko (Frontiers in Pediatrics, 2021)
Introduction: Umbilical catheterization provides a quick yet demanding central line that can lead to complications seen nowhere else. The aim of our study was to determine whether the repeated ultrasound scanning can influence the catheterization time, prevent some of the catheter-related complications, support the decision making process and allow prolonged catheterization in patients without an alternative central access route. Methods: A prospective observational study was performed in a tertiary neonatal intensive care unit. A total of 129 patients and 194 umbilical catheters (119 venous and 75 arterial) were analyzed with a total of 954 scans. Ultrasound screening consisted of 1) assessing the catheter tip, location, movability and surface and 2) analyzing the catheter trajectory. The outcome variables were defined as 1) catheter dislocation and 2) associated thrombosis. Results: Dislocation of catheter throughout the whole catheterization period was observed in 68% (81/119) of UVCs and 23% (17/75) of UACs. Thrombotic complications were observed in 34.5% (41/119) of UVCs and 12% (9/75) of UACs. ⅓ of UAC-associated thrombi were visible only after catheter removal. 51% (61/119) of UVC patients and 8% (6/75) of UAC patients made a clinical decision regarding the obtained catheter image. Conclusion: Bedside ultrasound imaging of catheters supports the decision-making process related to the catheterization duration, shortening the time if abnormalities are detected and allowing a safer prolonged UC stay when an alternative central line cannot be inserted.